TINJAUAN AKUMULASI SEFTRIAKSON DARI DATA URIN MENGGUNAKAN ELEKTROFORESIS KAPILER PADA PASIEN GANGGUAN FUNGSI GINJAL STADIUM TIGA - Suardi, Muslim; Raveinal, Raveinal; Sari, Lisa Oktia; Lailaturrahmi, Lailaturrahmi (Jurnal Ipteks Terapan, 2017)
Ceftriaxone is a third-generation cephalosporin which are excreted mostly via the kidneys. Drugs which are eliminated primarily by the kidneys may accumulate in the patients with impaired renal function. Ceftriaxone is widely used in DR.M.Djamil Hospital Padang. The dosage adjustment for this drug has not yet performed in the hospital so far. This study was conducted in patients who suffered from stage 3 renal failure, received ceftriaxone therapy, and were 20-65 years of age. Urine samples were collected from patients at 4, 4.5, 5.75, 6.5, 7.75, and 8.25 hours after drug administration. Samples were analyzed using capillary electrophoresis. The buffer used was sodium tetraborate with pH of 9, concentration of 50 mM and pKa 9,24. The absorbance of solutions were measured at wavelength of 241.2 nm. From the standard calibration curve of ceftriaxone, the equation of Y = 4.455x - 2.297 (R2 = 0.995), (SD =1.40) was obtained. The migration time of ceftriaxone was 9 minutes. The LOD and LOQ were 0.94 and 3.14 Âµg/mL, respectively. The elimination rate and elimination half life were 0.046/h and 15,06 h, respectively. Du cumulative and acumulation fraction of drugs were 365.10 mg and 0.33 (33%), respectively. Dmax and Dmin were 2.985 and 985 mg, respectively. Cmax and Cmin were 224,43 and 74,06 mg/L, respectively. The accumulation index of the drug was 1.49. Cl. AUC0Ë and the CpO were 0.612 L/h, 3.268 mg h/L and 150.37 mg/L, respectively. Impaired renal function may affect pharmacokinetic parameters such as elimination rate, elimination half-time, and drug clearance.Â Â